A Comparison of Two Ovine Lumbar Intervertebral Disc Injury Models for the Evaluation and Development of Novel Regenerative Therapies. Issue 8 (December 2018) - Daly, Chris D.; Ghosh, Peter; Badal, Tanya; Shimmon, Ronald; Jenkin, Graham; Oehme, David; Cooper-White, Justin; Sher, Idrees; Chandra, Ronil V.; Goldschlager, Tony
Study Design: Large animal research. Objective: Lumbar discectomy is the most commonly performed spinal surgical procedure. We investigated 2 large animal models of lumbar discectomy in order to study the regenerative capacity of mesenchymal stem cells following disc injury. Methods: Twelve adult ewes underwent baseline 3-T magnetic resonance imaging (MRI) followed by lumbar intervertebral disc injury by either drill bit (n = 6) or annulotomy and partial nucleotomy (APN) (n = 6). Necropsies were performed 6 months later. Lumbar spines underwent 3-T and 9.4-T MRI prior to histological, morphological and biochemical analysis. Results: Drill bit-injured (DBI) and APN-injured discs demonstrated increased Pfirrmann grades relative to uninjured controls ( P < .005), with no difference between the 2 models. Disc height index loss was greater in the APN group compared with the DBI group ( P < .005). Gross morphology injury scores were higher in APN than DBI discs ( P < .05) and both were higher than controls ( P < .005). Proteoglycan was reduced in the discs of both injury models relative to controls ( P < .005), but lower in the APN group ( P < .05). Total collagen of the APN group disc regions was higher than DBI and control discs ( P < .05). Histology revealed more matrix degeneration, vascular infiltration, and granulation in the APN model. Conclusion: Although both models produced disc degeneration, the APN model better replicated the pathobiology of human discs postdiscectomy. We therefore concluded that the APN model was a more appropriate model for the investigation of the regenerative capacity of mesenchymal stem cells administered postdiscectomy.